Importance of Remote Sensing Data in The Study of Land Resources - SH.Y.Sattorov; A.M.Abdulloyev; A.B.Ochilov; A.B.To’xtamishov (Indonesian Journal of Innovation Studies, 2022)
This article discusses the importance of remote sensing data in the study of land resources, through which the current production process is carried out directly